Diversion in Child Sexual Violence Cases: A Comparative Study of Indonesia and Norway - Irabiah Junus; Taslim Fait; Anis Ribcalia Septiana; Indar Ismail Jamaluddin; Yodang Yodang (Universitas Negeri Semarang, 2026)
This study examines the implementation of diversion in child sexual violence cases in Southeast Sulawesi, Indonesia, and compares it with restorative justice practices in Norway. Despite the growing adoption of diversion under Law No. 11 of 2012 on the Juvenile Criminal Justice System, its application in sexual violence cases remains controversial and inconsistent. Using a qualitative approach based on interviews and document analysis, this study finds that diversion practices in Indonesia are constrained by victims' consent, socio-cultural factors, and limited institutional capacity. At the same time, Norway demonstrates a more structured, welfare-oriented restorative model. The study highlights the need for clearer guidelines and stronger victim protection mechanisms to ensure a balanced approach to justice.